The Influence of Authoritarian and Democratic Leadership Styles on Organizational Climate in an Educational Environment - Rezky, Sri; Saragih, Rosvilani; Fahira, Rachyana; Lubis, Wildansyah; Winara, Winara (PT Inovasi Pratama Internasional, 2024)
The role of education in shaping a qualified and productive generation is of paramount importance. One of the key determinants of educational quality is the leadership style of the principal. This article seeks to examine the impact of the principal's authoritarian and democratic leadership styles on the organizational climate within the educational environment. This study employs a descriptive qualitative research approach utilising a questionnaire as a data collection instrument. The research population consisted of students enrolled at ABC School. The survey instrument was employed to assess the principal's leadership style and students' learning motivation. The findings of this study suggest that a principal's democratic leadership style exerts a positive and statistically significant influence on the organizational climate in the educational environment. In an educational setting under the guidance of a principal with a democratic leadership style, all members perceive themselves to be valued and engaged in an active role in the learning process. Conversely, a principal's authoritarian leadership style was found to have a negative impact on the school environment. This may result in a hindrance of roles and activities within the organizational environment.